INDEKS INKLUSI KEUANGAN SYARIAH DI INDONESIA TAHUN 2015-2018 - Sindi Puspitasari; A. Jajang W Mahri; Suci Aprilliani Utami (Univeristas Islam Bandung, 2020)
This research is based on the problem is the low involvement of the public in making transaction using Islamic banking service in Indonesia. This study aims to describe and measure the level of Islamic financial inclusion on the Islamic banking sector include Sharia Commercial Bank (BUS), Sharia Business Unit (UUS) and Rural Sharia Bank (BPRS) in Indonesia period 2015-2018 using Index of Financial Inclusion. There are three dimensions measured in this study dimensions of accessibility, availability and usage. This research was conducted in 33 provinces in Indonesia. The method used in this research is quantitative descriptive method. The results showed the level of sharia financial inclusion in 2015-2018 experienced a fluctuating development in which the average Index of shariah financial inclusion in Indonesia is the low category. From 33 provinces in Indonesia, DKI Jakarta included in the high category, Aceh and D.I Yogyakarta are in the medium category, and there are 30 provinces with low category. Nusa Tenggara Timur Province is a province with the lowest category during the study period. Generally, the dimensions index of shariah financial inclusion are the low category.